Optimization Of Dewatering Management Using Smart Iot Control – Multiflow On/Off Monitoring System (Sic-Mufs) At Pt. Ppa Jobsite Sks, October 2024 – March 2025 - Fikri, Muzayyinul; Noor, Ahmad; Anam, Choirul; Pratama, Agung Sedayu; Wijaya, Toni (Green Publisher Indonesia, 2026)
Global climate change is a critical issue affecting the sustainability of projects, especially in the mineral and coal mining industry. At PT Putra Perkasa Abadi, climate change was identified as the highest risk in the company's risk management profile, impacting mining operations. One significant effect is the inconsistency between planned and actual rain hours, leading to high rainfall, which hampers production and productivity targets. Dewatering management, which deals with rainwater filling the sump, is particularly affected. In extreme weather, workers must operate pumps, a high-risk activity near water. The increased frequency of pump operations during 2024’s high rainfall heightens accident risks. To mitigate this, the company developed SIC-MUFS, a tool that allows remote pump operation. This system enables workers to avoid crossing the sump in dangerous weather conditions and can also monitor the water level automatically. If the water reaches critical levels, SIC-MUFS sends notifications to the Central Control Room (CCR) for further action.